MRSA eradication of newly acquired lower respiratory tract infection in cystic fibrosis. Issue 1 (15th March 2016) - Vallières, Emilie; Rendall, Jacqueline C.; Moore, John E.; McCaughan, John; Hoeritzauer, Anne I.; Tunney, Michael M.; Elborn, Joseph Stuart; Downey, Damian G.
UK cystic fibrosis (CF) guidelines recommend eradication of methicillin-resistant Staphylococcus aureus (MRSA) when cultured from respiratory samples. As there is no clear consensus as to which eradication regimen is most effective, we determined the efficacy of eradication regimens used in our CF centre and long-term clinical outcome. All new MRSA positive sputum cultures (n=37) that occurred between 2000 and 2014 were reviewed. Eradication regimen characteristics and clinical, microbiological and long-term outcome data were collected. Rifampicin plus fusidic acid was the most frequently used regimen (24 (65%) out of 37 patients), with an overall success rate of 79% (19 out of 24 patients). Eradication failure was more likely in patients with an additional MRSA-positive peripheral screening swab (p=0.03) and was associated with worse survival (p=0.04). Our results demonstrate the feasibility and clinical benefits of MRSA eradication. As peripheral colonisation was associated with lower eradication success, strategies combining systemic and topical treatments should be considered to optimise outcomes in CF patients. In CF, eradication of MRSA from the respiratory tract is feasible and is associated with better clinical outcome http://ow.ly/YfbqD